Blue Light Induced Edible Mushroom (Lentinula edodes) Proteomic Analysis - Park, Youn Jin (J Fungi (Basel), 2020)
Blue light is an important environmental factor that induces mushroom growth and morphological changes. In this study, after confirming the morphological difference between Lentinula edodes (LE) under blue light condition (BL) and lightless condition (LL), the increase and decrease in LE protein and the expression of RNA of each protein were confirmed under each condition. LE specimens grown in BL and LL were identified by 253 spots in BL through 2D electrophoresis and LC-MSMS analysis, and 22 types of proteins were identified. It was confirmed that 14 types of proteins showed reduced expression in BL compared to LL. On the other hand, eight kinds of proteins with increased expression in blue light compared to LL were identified. As a result of confirming the difference from the expression pattern in 2D electrophoresis through Quantitative Real-Time PCR, it was confirmed that the expression pattern of the two proteins showed a difference. Therefore, this study will be a key study on the changes in mushroom morphology induced by blue light and the proteins that induce it.